Cover Picture: Revealing the Distribution of the Atoms within Individual Bimetallic Catalyst Nanoparticles (Angew. Chem. Int. Ed. 42/2014). Issue 42 (14th August 2014) - Felfer, Peter; Benndorf, Paul; Masters, Anthony; Maschmeyer, Thomas; Cairney, Julie M.
<x xml:space="preserve">Abstract</x> Slice by slice atom probe tomography data from a Au@Ag core–shell nanoparticle reveals the arrangement of the atoms throughout the particle. The Cover Picture shows the distribution of Au (yellow) and Ag (gray) atoms within a 15 nm nanoparticle, determined with near‐atomic resolution by T. Maschmeyer and co‐workers in their Communication on page 11190 ff. The elements are not evenly distributed across the surface, a result of surface morphology and of residues from the particle synthesis.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>